(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A distinctive anatomical and physiological feature of the eye's walls is the administration of optical medicine. The scientists were required to create novel phrasings to deliver medications to the eye at a controlled rate in order to avoid the need for repeated instillations due to the low optical bioavailability obtained from standard phrasings. The possibility of administering medications topically through the constrained precorneal area and releasing them gradually has been illustrated by natural polymers. Ideal ophthalmic drug delivery must be able to maintain drug release and stay in close proximity to the front of the eye for an extended period of time. Therefore, it is essential to improve the delivery of ophthalmic medications; one way to achieve this is by adding polymers of different colours, creating an in-place gel or colloidal suspension, or employing an erodible or non-erodible insert to prolong the pre corneal medication retention. In addition to polymer employed in modern pharmaceutical design and numerous potential routes of drug delivery into optical apkinsn, this review focused on controlled and sustained medicine delivery.